Network pharmacology and molecular docking analysis on molecular targets and mechanism prediction of Huanglian Jiedu Decoction in the treatment of COVID-19 - Xu Xinyi; Liu Leping; Cao Xueshuai; Long Xi; Peng Sujuan; Zhang Guomin (KeAi Communications Co., Ltd., 2022)
Objective: To investigate and predict the molecular targets and mechanism of Huanglian Jiedu Decoction (黄连解毒汤, HLJDD) in the treatment of Corona Virus Disease 2019 (COVID-19) through network pharmacology and molecular docking analysis. Methods: The chemical constituents and action targets of HLJDD were retrieved on Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), SymMap v2, Encyclopedia of Traditional Chinese Medicine (ETCM), a High-throughput Experiment- and Reference-guided Database of Traditional Chinese Medicine (HERB), and Traditional Chinese Medicine Integrated Database (TCMID). UniProt and GeneCards were used to query the target genes that corresponding to the active compounds, and then a compound-target network was constructed using Cytoscape 3.7.2. Gene Ontology (GO) database was used to annotate GO functions. Kyoto Encyclopedia of Genes and Genomes (KEGG) was used to predict the possible mechanisms of active compounds. The Database for Annotation, Visualization and Integrated Discovery (DAVID) was used to analysis the tissue enrichment. The main active compounds in HLJDD are molecularly docked with their corresponding related targets. Results: Seventy-six compounds were screened and 458 corresponding targets in the network were obtained. Gene annotation showed that the targets were involved mainly in 1953 biological processes. 884 signaling pathways was enriched, involving signaling by interleukins, cytokine signaling in immune system, generic transcription pathway, and RNA polymerase II transcription. The targets mainly distributed in the lung, liver, and placenta, involving a variety of immune cells, such as T cells and B cells. The molecular docking results showed that core compounds such as wogonin, berberine, and baicalein had high affinity with tumor necrosis factor (TNF), insulin (INS), and tumor protein 53 (TP53). Conclusion: The active compounds in HLJDD may have a therapeutic effect on COVID-19 through regulating multiple signal pathways by targeting genes such as vascular endothelial growth factor A (VEGFA), INS, interleukin-6 (IL-6), TNF, caspase-3 , TP53, and mitogen-activated protein kinase 3 (MAPK3).